A new ground motion prediction model for Northeast India (NEI) shallow crustal. Issue 1 (June 2020) - Rahman, T; Nunia, Bindesh
Abstract: In this paper, a new ground-motion prediction model (GMPE) for North-eastern India (NEI) is developed based on the available recorded events. NEI has already faced several high magnitude earthquakes (moment magnitude [ Mw ]>7.0) during the period 1200 to 2018. It is difficult to develop GMPE and estimating the seismic hazard of NEI, due to sparse recorded strong motion database. To date, seismic hazard maps for NEI have not been prepared. All developed countries have developed seismic hazard maps for their cities using region-specific GMPE. So, to prepare the seismic hazard maps of NEI, a ground motion prediction model will be required. The success of earthquake hazard mitigation depends to a large extent on how accurately the ground motion hazard can be estimated at a vulnerable site. The GMPE developed in this study has been compared with other ground-motion models as well as with the available limited recorded strong motion database. Based on the comparison, it is observed that the new model is reasonably correct as the model is unbiased with respect to both magnitude and hypocentral distance. This model needs to be upgraded as and when more recorded strong ground motion database is available for this region.